Global assessment of manure management policies and practices - Teenstra, E.; Vellinga, Theun V.; Aektasaeng, N.; Amatayakul, W.; Ndambi, A.; Pelster, David E.; Germer, L.; Jenet, A.; Opio, C.; Andeweg, K. (Wageningen University & Research, 2014)
In 2014 an assessment of livestock manure policies was performed in 34 countries in Asia, Africa and Latin America, followed by an in-depth assessment of manure management practices in Bangladesh, Viet Nam, Ethiopia, Malawi, Argentina and Costa Rica. The assessments revealed the key barriers for improving integrated manure management and identified six opportunities for actual practice changes to improve manure related policies as well as farm practices with the overall objective of improving food security while mitigating methane emissions at the same time